The Existence of Islamic Book Publishers in Medan City (1950-1990) - Saidatul Khairiyah; Haidar Putra Daulay; Hasan Asari (Sekolah Tinggi Agama Islam Al Hidayah, 2021)
Book publishers are a symbol of progress and civilization. The city of Medan was once the